KESEHATAN LINGKUNGAN DAN KEBERLANJUTAN KOTA MEDAN: EVALUASI TERHADAP KUALITAS AIR DAN KESEJAHTERAAN MASYARAKAT - ALEX MARULI TUA LUMBANRAJA (JURNAL ILMIAH KOHESI, 2022)
Medan City is a city that has a chaotic urban planning and layout, where the development carried out does not pay attention to environmental health conditions, as well as the lack of insight and checking of water conditions, as well as the environment of people who still live in an environment that is not clean and orderly has an impact on the lack of improvement in the quality of life, and decreases the welfare of the community. This study used descriptive longitudinal analytical method. The population of this study amounted to 29,100 people who experienced reproductive health problems, where reproductive health problems would cause sexual diseases. The population of this study amounted to 1,450,000 residents who owned housing in Medan City, where the sample taken amounted to 72 residents who owned housing in Medan City. The results of the study stated that the number of residents who have unhealthy categorized housing is in East Medan District, which causes a worsening of environmental health improvement due to the Government's lack of readiness in determining water quality that is not up to standard, as well as the deterioration of development sustainability due to the response of the Medan City Government by establishing residential areas that are in an environment that is not neat and clean.